2018
DOI: 10.1016/j.semcancer.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer stem cells: A state or an entity?

Abstract: Pancreatic ductal adenocarcinoma (PDAC), the most common type of pancreatic cancer, has a median overall survival of 6-12 months and a 5-year survival of less than 7%. While PDAC currently represents the 4th most frequent cause of death due to cancer worldwide, it is expected to become the second leading cause of cancer-related death by 2030. These alarming statistics are primarily due to both the inherent chemoresistant and metastatic nature of this tumor, and the existence of a subpopulation of highly plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 114 publications
(119 reference statements)
1
76
0
Order By: Relevance
“…Thus, from a clinical perspective, the effective targeting and elimination of CSCs should lead to tumor elimination. Unfortunately, since their discovery in acute myeloid leukemia in 1994 [ 4 ], the development of anti-CSC-specific therapies has proven difficult due to the genetic and nongenetic factors underlying the inherent CSC state and the plasticity that exists between CSCs and non-CSCs [ 5 ]. As a consequence, to date, only a handful of anti-CSC-specific therapies exist, but many promising therapies are in clinical trials (reviewed in Yang et al [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, from a clinical perspective, the effective targeting and elimination of CSCs should lead to tumor elimination. Unfortunately, since their discovery in acute myeloid leukemia in 1994 [ 4 ], the development of anti-CSC-specific therapies has proven difficult due to the genetic and nongenetic factors underlying the inherent CSC state and the plasticity that exists between CSCs and non-CSCs [ 5 ]. As a consequence, to date, only a handful of anti-CSC-specific therapies exist, but many promising therapies are in clinical trials (reviewed in Yang et al [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine has been identified as a potent proinvasive factor (Siriwon et al, 2018), and it is a strong stimulator of Treg immunosuppressive activity (Ghalamfarsa et al, 2018) and a suppressor of CTLs (Y. . Cross-talking between CSCs with other cells within TME has been shown in proliferative rates and are not responsible for long-term tumor growth (Batlle & Clevers, 2017;Hermann & Sainz, 2018). There is evidence that residual tumors are frequently enriched with CSCs, so the cells are essentially responsible for tumor rebound after therapy (Cazet et al, 2018).…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…It is well known that PDAC is composed of both undifferentiated or poorly differentiated cancer stem cells and more differentiated malignant cells that are derived from cancer stem cells. 20 Since we is depicted in Figure 3A. Interestingly, a significant increase in the percentage of side cell population (SP) was observed in T3M4 SC cells (1.57% ± 0.22) when compared with WT cells (0.54% ± 0.05) (P = 0.0163).…”
Section: Truncation Of O-glycans Enhance the Stemness Feature Of Pdmentioning
confidence: 77%
“…It is well known that PDAC is composed of both undifferentiated or poorly differentiated cancer stem cells and more differentiated malignant cells that are derived from cancer stem cells . Since we found that cancer‐specific truncation of O‐glycans enhanced the oncogenic features through the induction of EMT, we sought to explore the possibility of truncated O‐glycans induced stem cell side populations in PDAC cells as EMT is closely associated with cellular plasticity .…”
Section: Resultsmentioning
confidence: 99%